Prespektif Islam Social Finance In Poverty Alleviation Efforts In Indonesia - imama zuchroh (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2021)
The world's poverty rate continues to creep up. The vortex of waves continues to roll the countries impacted by the corona pandemic. Indonesia's efforts from year to year to reduce poverty are in vain and even its progress or achievements have instantly vanished. Indeed poverty and inequality are global phenomena but increasing these conditions are a major threat. Poverty shows a lack of income and needed ways to achieve a better standard of living. Islam social Finance has played an important role in helping reduce poverty and inequality through assistance to the community or people. Therefore, this research through the study literature method explores the role of Islamic social finance as an alternative way to reduce poverty and inequality. And this is expected to contribute to the country's economic development.